Mother’s tongue and father’s culture; A late nineteenth-century Javanese versification of Master Zhu’s Household Rules (Zhuzi Zhijia geyan) - Wieringa, Edwin P. (UI Scholars Hub, 2020)
The Serat Tiyang Gegriya or “Book for people on running their homes and households” is a Javanese versification of the famous seventeenth-century Chinese treatise Zhuzi Zhijia geyan (‘Master Zhu’s Household Rules‘), better known in the Anglophone world as “Maxims for managing the home” or “Family regulations”. Propagating the basic principles of Confucian ethics, this small treatise instructed generations of Chinese readers, presumedly adult males, lessons in proper behaviour. Today, Master Zhu’s little compendium is among the most reprinted works of classical Chinese popular literature. The Serat Tiyang Gegriya exists in the form of a manuscript, written in Surabaya in 1878, and was subsequently published ten years later in the same city. The appearance of this popular Confucian tract in Javanese seems to have been born of a perceived sense of crisis and alarm at the decline of “Chineseness” among the Chinese minority in a foreign land, the upshot of the seemingly inexorable process of acculturation taking place in the Sino-Javanese community at the end of the nineteenth century. Paradoxically, however, the Serat Tiyang Gegriya itself is a fine product of acculturation, transmitting Chinese moral teachings in the form of the Javanese piwulang genre, or lessons on how to live a good life, composed in the mother tongue of the mothers of the intended readers as this group was unable to understand Chinese, the language of their fathers and paternal ancestors.